De como as Américas foram monstrificadas: a imagética da teratologia do novo mundo no século XVI - Andrade, Fernanda Jardim de Farias (2023)
This dissertation aims to understand the discursive stage that moved between imagistic semiotics, description and narration, which interacted in a trade that exploited models and references that were necessarily known and guaranteed the minimum intelligibility of something so different. The authors who make up the characters in this dissertation were chosen because they are a good sample or good representatives of the various 16th century political projects for the Americas. Four authors from different decades of the same century, with divergent ideals, defending different projects for the New World. Pero de Magalhães Gândavo, Jean de Léry, André Thevet and Walter Raleigh are the main characters in the narrative of this dissertation. They project the monsters of their imaginations and their imaginations onto the New World, preferably - but not exclusively - based on the elements bequeathed by the literature of Greek, Latin and Greco-Latin Classical Antiquity. But these prodigious beings were not only evoked to think negatively or positively about the world that was unfolding - to use a recurring image from the 17th to the 19th century - but also, at the same time, to exalt and demean their adversaries. The idea of exalting by demeaning, demeaning by exalting, is as old as the Iliad itself. Like Heracles, Perseus, Theseus or Odysseus, the monster fighter becomes as much of a hero as the monster.